Síntese de Calcogenofenos e Isoquinolinas via Reações de Ciclização Intramolecular - Stein, André Luiz Agnes (2013)
In the first part of this work, a series of selenophenes and tellurophenes were prepared starting from of (Z)-chalcogenoenynes, by employing FeCl3 diorganyl dichalcogenide-mediated intramolecular cyclization. In general, the cyclic products were obtained in moderate to good yields. In order to evaluate the versatility of the obtained 3-chalcogen selenophene derivatives, we tested the reactivity of these compounds toward halogenation and Li/Se exchange reactions. In this way, the reaction of 2,5-diphenil-3-(fenilselene)-selenofene with an excess of bromine, afforded the resultant product in 86% yield. In addition, the reaction of 2,5-diphenil-3-(butilselene)selenofene with n-butyllithium gave the lithiated species. The lithiated species was trapped by aldehydes affording the secondary alcohols in 68 to 73% yield. In a second stage, we developed an alternative method to promote the intramolecular cyclization of o-alkynyl benzaldimines 3, by employing CuI and differently substituted diorganoyl diselenides as promoter agents of this process. Through this cyclization protocol we could satisfactory synthesize a series of 4-organochalcogen-isoquinolines 4 in good yields. Finally, the presence of an organochalcogen substituent in the isoquinoline structure allowed further structural elaboration through conversion of the chalcogen group into other substituents. In this sense, when the 4-(buthyltelluro)-3-phenylisoquinoline was applied to the tellurium lithium exchange conditions, followed by reaction with aldehydes, the corresponding secondary alcohols were obtained in high yields. Furthermore, we have also successfully applied this isoquinoline as a substrate in Suzuki and Sonogashira coupling conditions affording the corresponding products moderate to good yields.